Enhancement of learning capabilities of students of all ability levels through a constructivist approach - Samandra, Ranjith A. (Curtin University, 2013)
This is an analytical examination of academic constructivism and a critical inquiry into the development of my own practice as a learner-educator. Therefore, this work invariably involved a punctilious look at the epistemological foundations of constructivism and an assiduous scrutiny of my own axiomatic belief system. In this wandering-pilgrimage, I have traversed from my Year 9 naïve academic constructivism to an ever-evolving plurality of epistemologies and academic approaches which are hopefully interwoven with right mindfulness.